Detección de introgresión en la perdiz roja (Alactoris rufa), mediante marcadores moleculares de tipo RAPD - Ramiro García, Javier; Sevane Fernández, Natalia; García-atance Fatjó, María Asunción (Revista Complutense de Ciencias Veterinarias, 2007)
In recent years, the use of the red-legged partridge (Alectoris rufa) for cynegenetic purposes has increased dramatically, and captive-bred individuals are released to reinforce wild populations. A problem appears at the farm level where partridges can be crossed with non-native species that are better adapted to captivity, like Alectoris chukar. In this study we use a set of eight RAPD markers to identify a possible hybridization of A.rufa with A.chukar partridges. A total of 1510 individuals were analysed, grouped into pools of five birds each. We obtained a frequency of genetic introgression in red-legged partridge near to 50%. These results show that a high percentage of hybridization in captive populations of Spanish partridges is present, and that more thorough control systems should be established in breeding farms for re-stocking purposes.